Selective and scalable oxygenation of heteroatoms using the elements of nature: air, water, and light - Diprima, Damiano; Gemoets, Hannes; Bonciolini, Stefano; Van Aken, Koen (Beilstein Journal of Organic Chemistry, 2023)
Sustainable oxidation protocols aim to provide an environmentally friendly and cost-effective method for the production of various chemicals and materials. The development of such protocols can lead to reduced energy consumption, fewer harmful byproducts, and increased efficiency in industrial processes. As such, this field of research is of great importance and interest to both academia and industry. This work showcases a sustainable and catalyst-free oxidation method for heteroatoms (e.g., S, P, and Se) using only air, water and light. An additional reaction pathway is proposed in which the incorporated oxygen on the heteroatoms originates from water. Furthermore, the addition of certain additives enhances productivity by affecting kinetics. The industrial potential is demonstrated by conveniently transferring the batch protocol to continuous flow using the HANU flow reactor, indicating scalability and improving safety.
Keywords: catalyst-free; flow chemistry; oxygen; photochemistry; sustainable oxidation